2008
DOI: 10.1016/j.jaci.2008.07.007
|View full text |Cite
|
Sign up to set email alerts
|

Corticosteroid-resistant asthma is associated with classical antimicrobial activation of airway macrophages

Abstract: Background The cause of corticosteroid resistant asthma is unknown. Objective To perform gene microarray analyses using BAL cells from well-characterized corticosteroid resistant (CR) and sensitive (CS) asthmatics to elucidate the differential expression of genes that contribute to the development of corticosteroid resistance. Methods The patients were characterized as CR or CS based on FEV1% predicted improvement after one week course of oral prednisone. Expression of selected gene targets was verified by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
124
0
3

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 144 publications
(134 citation statements)
references
References 51 publications
7
124
0
3
Order By: Relevance
“…It can be demonstrated in peripheral blood mononuclear cells and alveolar macrophages, and in resident cells such as airway smooth muscle cells from patients with severe asthma [166][167][168][169], but the relationship of these in vitro studies to in vivo responses is not well understood. Corticosteroid insensitivity has been associated with different comorbid conditions such as obesity [170], smoking [171], low vitamin D levels [172,173], and non-eosinophilic (low-Th2 inflammation) mainly in adults [174].…”
Section: Using Established Asthma Medications Corticosteroid Insensitmentioning
confidence: 99%
“…It can be demonstrated in peripheral blood mononuclear cells and alveolar macrophages, and in resident cells such as airway smooth muscle cells from patients with severe asthma [166][167][168][169], but the relationship of these in vitro studies to in vivo responses is not well understood. Corticosteroid insensitivity has been associated with different comorbid conditions such as obesity [170], smoking [171], low vitamin D levels [172,173], and non-eosinophilic (low-Th2 inflammation) mainly in adults [174].…”
Section: Using Established Asthma Medications Corticosteroid Insensitmentioning
confidence: 99%
“…LPS is a major component of the cell walls of Gram-negative bacteria and of allergens that trigger asthma. High levels of LPS have been detected in the bronchoalveolar lavage fluid (BALF) from steroidresistant asthmatics and are an important determinant of the severity of asthma (9,17). We and others have shown that IFN-g-producing cells and LPS contribute to the induction of airway inflammation and AHR in mouse models; furthermore, we have demonstrated that IFN-g/LPS-induced responses are steroid resistant (18,19).…”
mentioning
confidence: 67%
“…Although pulmonary macrophages are known to be critical in host defense against respiratory infection and are activated in the airways of asthmatics (51), their contribution to the disease process and the development of AHR is unclear. Exposure to Ags or increased level of LPS in the airways is associated with the activation of macrophages in asthma (17,48). Interestingly, the levels of CD11b + macrophages in the lung are almost doubled after allergen challenge in patients with asthma (48).…”
Section: Discussionmentioning
confidence: 99%
“…Acute exacerbations of asthma, often triggered by respiratory bacterial or viral infections, are critical clinical problems for asthma management and treatment. High levels of LPS and Th1 cytokine IFN-g have been detected in the airways of asthmatics, which are often correlated with asthma severity (3)(4)(5)(6)(7). LPS and IFN-g are two key mediators for exacerbative inflammatory responses and the decrease in sensitivity to steroid in experimental models of asthma (7)(8)(9).…”
mentioning
confidence: 99%